Italian pilot version of DEMOQL-PROXY: Content and Face validity: a methodological bridge for a future Italian validation - Miraglia Raineri, Alessandra (Acta Biomed, 2020)
BACKGROUND AND AIM OF THE WORK. The assessment of Quality of Life through validated tools allow to improve level of assistance for people suffering from Dementia. To our Knowledge in Italian language seem to be absent a tool to evaluate mild and moderate dementia, consequently underestimating and underrating needs of this specific target. We show an Italian pilot version of the DEMQOL-PROXY (specific for mild and moderate Dementia) testing some psychometric properties as: back-translation, content validity and face validity in Italian language. METHOD. A back-translation by two bilingual authors was presented. Was enrolled an expert panel to test Content Validity composed by eight Medical Doctor and a panel of six participants was recruited to assess Face Validity (three professional caregivers and three family caregivers) related to patients with moderate Dementia (with 10 to 20 MMSE, mild and moderate Dementia). RESULTS. Each item has a degree of agreement between experts of more than 70% and the Total CVI score is .90 (90% of agreement). So, in line with these results we can accept the version of items proposed. As regard Face Validity, the items of the instrument seem to be clear, without difficulty and there are no questions consiedered offensive or irritating. CONCLUSION. The Italian version of the DEMQOL-PROXY showed good psychometric properties: its structure and the results it leads to are similar to the original version and to the other translations produced so far. For this reason, we consider this paper as a methodological bridge for a future complete Italian Validation. (www.actabiomedica.it)